World Class University: A Literature Synthesis - Johan K. Runtuk (President University, 2016)
Discussions and debates about world class university (WCU) continue to increase. Various policies to realize the WCU have been formulated by universities, as well as by governments. To date, however, there has been no consensus about the substance of WCU. This research aims to answer some fundamental questions about WCU, i.e. definition, characteristics, and criteria. The findings revealed that there are some similarities in the understanding of the substance of the WCU. Universities must improve its quality, by continuing to recognize customers’ needs and expectations. Improvement in all things, both in terms of academic and non academic at the university should be pursued persistently.